Material technology receives green light from MQA! - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Muhammad Najib, Muhammad Nor (Penerbit UMP, 2011)
GAM BANG February 16, 2011 - The Faculty of Industrial Sciences & Technology, has received quality certification from Malaysian Qualification Agency (MQA) for the newly proposed academic program,Bachelor of Applied Science (Hons)MolecuMaterial Technology.